A case study of the gears and craft used for artisanal fishing in Chittagong Patharghata Fishery Ghat, Bangladesh and socio-economic condition of the fishermen (Asian Journal of Medical and Biological Research, 2017)
The Patharghata Fishery Ghat in Chittagong is one of the largest fish landing centers in Bangladesh. The study aimed to explore different types of gears and crafts used from the landing center, fish species caught by the gears, and certain degree of socio-economic condition of the fishermen. Data were collected from local fishermen through on the spot inspections, Personal Interview (PI), and Focus Group Discussion (FGD). The gears used from the landing center were classified as Large Mesh Drift Gill Nets (DGNs), Marine Set Bag Nets (MSBNs), and Trammel Nets. Mainly 7 types of DGNs having the mesh sizes ranging from 2.5 to 16 inches had been used by the fishermen of which Lakkha Jal, Lal jal and Char Shuta Jal were the most commonly used DGNs to catch Hilsha, Lakhua, Pomfret etc. Hilsha Shad (Tenualosa ilisha) was the most dominant species and about 60% of different nets were used to catch this species. Only single type of artisanal fishing craft (trawlers) was found in the landing center and is propelled by inboard engine. The capacity of the trawlers varied from 8 to 22 metric tons. In case of socio-economic condition, most of the fishermen belonged to the age groups of 21-30 and 31-40 years; each represented 31% of the total fishermen. About 91% of fishermen were found to be Muslim and rest 9% were Hindu. The average members of the nuclear and joint families were 3.78 and 7.83 per household, respectively; however, these groups of people were being deprived in their society. The study also revealed that about 67% of fishermen had no formal education and 27% had primary and rest 6% had secondary level of education. The annual income of the fishermen ranged from BDT 50,000 to 100,000 and the main expenditure of their earnings were for food (80%), followed by physical treatment (10%) of their family members. They had hardly any savings. Lack of knowledge and government support, and illiteracy were the major problems of the fishermen in the landing center.Asian J. Med. Biol. Res. December 2016, 2(4): 712-726